Molecular regulation of skeletal muscle mass and the contribution of nitric oxide: A review. Issue 6 (11th April 2019) - Kobayashi, Jun; Uchida, Hiroyuki; Kofuji, Ayaka; Ito, Junta; Shimizu, Maki; Kim, Hyounju; Sekiguchi, Yusuke; Kushibe, Seiji
Abstract: A variety of internal and external factors such as exercise, nutrition, inflammation, and cancer‐associated cachexia affect the regulation of skeletal muscle mass. Because skeletal muscle functions as a crucial regulator of whole body metabolism, rather than just as a motor for locomotion, the enhancement and maintenance of muscle mass and function are required to maintain health and reduce the morbidity and mortality associated with diseases involving muscle wasting. Recent studies in this field have made tremendous progress; therefore, identification of the mechanisms that regulate skeletal muscle mass is necessary for the physical and nutritional management of both athletes and patients with muscle wasting disease. In this review, we present an overall picture of the interactions regulating skeletal muscle mass, particularly focusing on the insulin‐like growth factor‐I (IGF‐I)/insulin‐Akt‐mammalian target of rapamycin (mTOR) pathway, skeletal muscle inactivity, and endurance and resistance exercise. We also discuss the contribution of nitric oxide (NO) to the regulation of skeletal muscle mass based on the current knowledge of the novel role of NO in these processes.